Symmetric Division Degree Invariants of Join Total and Mid Graphs - Murugarajan, P. (Communications in Mathematics and Applications, 2023)
The symmetric division degree (SDD) invariant is one of the 200 discrete Adriatic indices introduced several years ago. This SDD invariant has already been proven a valuable invariant in the QSAR (Quantitative Structure Activity Relationship) and QSPR (Quantitative Structure Property Relationship) studies. In this article, we present the bounds for SDD invariant of join total graph and SDD invariant of mid graphs.